Phlorotannins–bioactivity and extraction perspectives - Kumar, Lekshmi R. G.; Paul, Preethy Treesa; Anas, K. K.; Tejpal, C. S.; Chatterjee, N. S.; Anupama, T. K.; Mathew, Suseela; Ravishankar, C. N. (Journal of applied phycology, 2022)
Phlorotannins, a seaweed based class of polyphenolic compounds, have proven to possess potential bioactivities such as antioxidant, antimicrobial, anti-allergic, anti-diabetic, anti-inflammatory, anti-cancerous, neuroprotection etc. These bioactivities have further increased demand globally and sustainable techniques such as supercritical fluid extraction, microwave assisted extraction, enzyme assisted extraction, extraction using deep eutectic solvents etc. are being explored currently for production of phlorotannin-rich extracts. In spite of such well documented bioactivities, very few phlorotannin-based nutraceuticals are available commercially which highlights the significance of generating consumer awareness about their physiological benefits. However, for industry level commercialization accurate quantification of phlorotannins with respect to the different classes is vital requiring sophisticated analytical techniques such as mass spectrometry, 1 H-NMR spectroscopy etc. owing to the wide structural diversity. This review summarizes the extraction and bioactivities of phlorotannins based on the findings of in vivo and in vitro studies.